The effect of locally source carbonaceous materials on the mechanical properties of mild steel - Isaac Enesi, Dongo; S. Ojo, Seidu; Friday John, Ogbodo (International Journal of Engineering and Technology, 2016)
The work focuses on the effects of locally sourced carbonaceous materials such as Animal bone, Snail shell and Periwinkle Shell on the mechanical properties of mild steel carburized at varying treatment temperatures of 700, 800, 900, 1000 and 1100 Â°C, soaked at varying carburizing time of 5hr, 4hr, 3hr, 2hr and 1hr at the respective treatment temperatures. The samples are quenched in oil and tempered at 350Â°C for 45 minutes. Prior to the carburization process, standard test samples were prepared from the as received specimen for tensile tests, wear test and micro hardness analysis. After the carburization process, the test samples were subjected to standard test to generate data for ultimate tensile strength, the case and core hardness values, wear rate and wear resistance of the carburized samples. The study shows that the mechanical properties of mild steels were found to be strongly influence by each of the carbonaceous materials.